2013
DOI: 10.1038/ejhg.2013.25
|View full text |Cite
|
Sign up to set email alerts
|

Fetal polymorphisms at the ABCB1-transporter gene locus are associated with susceptibility to non-syndromic oral cleft malformations

Abstract: ATP-binding cassette (ABC) proteins in the placenta regulate fetal exposure to xenobiotics. We hypothesized that functional polymorphisms in ABC genes influence risk for non-syndromic oral clefts (NSOC). Both family-based and case-control studies were undertaken to evaluate the association of nine potentially functional single-nucleotide polymorphisms within four ABC genes with risk of NSOC. Peripheral blood DNA from a total of 150 NSOC case-parent trios from Singapore and Taiwan were genotyped, as was cord bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…The haplotype of ABCB1 in conjunction with sex is correlated with the risk of extrarenal adverse effects resulting from MPA [49] . Mothers who carry the ABCB1 3435C > T polymorphism are at significantly increased risk for having offspring with CLP, especially mothers using medication in the periconceptional period; [50] this risk is presumably attributable to suboptimal exclusion of xenobiotics at the fetal–maternal interface [51] …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The haplotype of ABCB1 in conjunction with sex is correlated with the risk of extrarenal adverse effects resulting from MPA [49] . Mothers who carry the ABCB1 3435C > T polymorphism are at significantly increased risk for having offspring with CLP, especially mothers using medication in the periconceptional period; [50] this risk is presumably attributable to suboptimal exclusion of xenobiotics at the fetal–maternal interface [51] …”
Section: Discussionmentioning
confidence: 99%
“…[49] Mothers who carry the ABCB1 3435C > T polymorphism are at significantly increased risk for having offspring with CLP, especially mothers using medication in the periconceptional period; [50] this risk is presumably attributable to suboptimal exclusion of xenobiotics at the fetal-maternal interface. [51] 4.3. COL1A1 could be involved in Stickler syndrome, similar to MPA-induced CLP COL1A1 encodes the alpha 1 chain of collagen type I, which can be inhibited by MPA.…”
Section: Tp53 and The Associated Mdm2 And Rpl5 Genes May Be Involved ...mentioning
confidence: 99%
“…Additionally, el-Ashmawy, I. M. et al, [28] observed that verapamil could dramatically enhance the susceptibility of fetal developmental disorders induced by ivermectin via P-gp inhibition. With regard to clinical studies, two researches [31, 32] have reported that 3435C>T polymorphism of ABCB1 gene could affect the risk of toxicants-induced birth defects, which might be explained by the alteration of placental P-gp expression and efflux activity. Moreover, a recent epidemiological case-control survey [33] documented that several drug classes that are substrates for P-gp were shown to have a higher user rate in mothers of cases with specific anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…Reliable associations of gene variations (IRF6, MDR1, and MTHFR) with an increased risk for CLP, CL, and CP have been obtained in different populations. (1)(2)(3)(4)(5) IRF6 is a protein encoded by the IRF6 gene in humans. This gene encodes a member of the interferon regulatory transcription factor family.…”
Section: Introductionmentioning
confidence: 99%
“…These proteins are able to remove toxins or drugs from the environment that enter the mother's body, into the mother's bloodstream, and can lead to an altered response of the fetus on xenobiotics and a subsequent increase in the risk of complex genetic disorders or birth defects. (3) The MTHFR gene, encoding the synthesis of the MTHFR enzyme, is located on chromosome 1p36.3. MTHFR plays a key role in folic acid metabolism.…”
Section: Introductionmentioning
confidence: 99%